A Spitzer-IRS search for the galaxies that re-ionized the Universe - Lacy, M; Bunker, A; Kneib, J; Teplitz, H (2006)
We describe an observation designed to find H emission from galaxies at z712 made using the InfraRed spectrograph (IRS) on the Spitzer Space Telescope. © 2007 International Astronomical Union.